Inventarisasi Keragaman Musuh Alami Erionota Thrax L. pada Beberapa Jenis Tanaman Pisang Bermikoriza di Desa Sampali - Pasrah Imanuel; Suswati Suswati; Asmah Indrawaty (Universitas Medan Area, 2021)
Banana cultivation will not be separated from pest problems. One of the main pests that attack banana plants is the banana leaf rolling caterpillar Erionota thrax L. The research was carried out in the Unified Community Farmer Group of Sampali Village, Percut Sei Tuan District, Deli Serdang Regency in March-May 2020. The research method used was descriptive analysis method using random sample (random sampling). The observation parameters consisted of population density, level of pest attack, egg parasitoid, larval parasitoid, pupa parasitoid, parasitoid identification, species diversity index, species evenness index, and relative abundance. There are 4 types of parasitoids, namely Braconidae sp 1 (Hymenoptera: Braconidae), Tachinidae sp 1 (Diptera: Tachinidae), Xanthopimpla gampsura (Hymenoptera: Ichneumonidae) and Brachymeria lasus Walker (Hymenoptera: Chalcididae). Erionota thrax L. parasitoid diversity index 0.7929 in low diversity levels, and the highest relative abundance of Brachymeria lasus Walker 98%, Erionota thrax attack rates on Barangan bananas reached 36.51%, Erionota thrax attack rates on Kepok bananas reached 45.13% , the attack rate of Erionota trax on Roti bananas was 50.72%, while the attack rate of Erionota thrax on FHIA-17 bananas was 42.46%.